Pattern recognition for ultraviolet and fourier transform data: A walkthrough of techniques and direction - Nur Hasshima Hasbi; Abdullah Bade; Chee Fuei Pien (Faculty of Science and Natural Resources, 2021)
Pattern recognition has been a booming area of studies in many applications especially in spectral data classification involving gigantic and complex data. Pattern recognition aimed to extract pattern from the data and differentiate the gathered data to produce new form of description and pattern. This paper presents a walkthrough of pattern recognition techniques for spectral data mainly the Ultraviolet (UV) and Fourier Transform Infrared (FTIR) data. This paper will also discuss the current trend analysis, challenges, and probable future approaches for pattern recognition field of study with special focus on UV and FTIR domain.